2013
DOI: 10.1080/00218464.2013.768123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Argon Plasma Pretreatment on Tensile Bond Strength of a Silicone Soft Liner to Denture Base Polymers

Abstract: This study evaluated the effect of argon plasma treatment on tensile bonding of heat-cured and auto-polymerized acrylic resins prior to the processing of a silicone soft liner. Both types of polymethylmethacrylate (PMMA) resins were treated with argon plasma for 1 min or 10 min (n ¼ 5). A control group, including untreated resin specimens, was also formed. After processing of the soft liner, the specimens were deflasked and stored dry for 24 h, and they were then subjected to tensile bond strength testing. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The main aim of the above repair is the improvement of structure strength, which is influenced by the strength of composite patch/damaged structure bonding. Recently, plasma, commonly denoted as 'the fourth state' and comprising a large number of charged particles, has been successfully used to treat and repair damaged composites [4][5][6]. Importantly, plasma treatment of material surfaces can improve their activity by inducing oxygenation and thereby enhancing the interfacial bonding properties.…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of the above repair is the improvement of structure strength, which is influenced by the strength of composite patch/damaged structure bonding. Recently, plasma, commonly denoted as 'the fourth state' and comprising a large number of charged particles, has been successfully used to treat and repair damaged composites [4][5][6]. Importantly, plasma treatment of material surfaces can improve their activity by inducing oxygenation and thereby enhancing the interfacial bonding properties.…”
Section: Introductionmentioning
confidence: 99%
“…The ease of processing and low production cost also contributes to their widespread application. Its biocompatibility makes PMMA highly attractive material in medicine either as drug delivery agent, eye‐ and contact glasses, orthopedic surgery, or dentistry, but especially as intraocular lenses . One of the main concerns of their use as implant is its hydrophobic nature.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main disadvantage of siliconebased soft liner materials is the deterioration of the bond over time due to their structural differences with PMMA. 5 The tensile bond strength (TBS) between liner and heat polymerized PMMA is important for its service life. 6 Due to the poor adhesion both functional and hygienic problems may occur as a result of the soft liner separating from denture base.…”
mentioning
confidence: 99%
“…Plasma has played an effective role in increasing surface wettability, surface energy, hydrophilic properties as well as killing a variety of pathogens. 5,13,18 Since the depth of the plasma treatment is limited to a few nanometers of the material surface, it is a useful method where surface modifications can be made without affecting the physical properties and function of the material. 15,19 Recently, studies on plasma technology in surface modification of PMMA have been reported and its application has been recommended as an increase in the TBS of the soft liner to PMMA has been observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation